Ocular blood flow and choroidal thickness changes after carotid artery stenting - BALTACIOĞLU, FEYYAZ; MİDİ, İPEK; ERASLAN, MUHSİN (CONSEL BRASIL OFTALMOLOGIA, 2020)
Purposes: To evaluate changes in ocular blood flow and subfoveal choroidal thickness in patients with symptomatic carotid artery stenosis after carotid artery stenting. Methods: We included 15 men (mean age, 63.6 +/- 9.1 years) with symptomatic carotid artery stenosis and 18 healthy volunteers (all men; mean age, 63.7 +/- 5.3 years). All participants underwent detailed ophthalmologic examinations including choroidal thickness measurement using enhanced depth-imaging optic coherence tomography. The patients also underwent posterior ciliary artery blood flow measurements using color Doppler ultrasonography before and after carotid artery stenting. Results: Patients lacked ocular ischemic symptoms. Their peak systolic and end-diastolic velocities increased to 10.1 +/- 13.1 (p=0.005) and 3.9 +/- 6.3 (p=0.064) cm/s, respectively, after the procedure. Subfoveal choroidal thicknesses were significantly thinner in patients with carotid artery stenosis than those in the healthy controls (p=0.01). But during the first week post-procedure, the subfoveal choroidal thicknesses increased significantly (p=0.04). The peak systolic velocities of the posterior ciliary arteries increased significantly after carotid artery stenting (p=0.005). We found a significant negative correlation between the mean increase in peak systolic velocity values after treatment and the mean preprocedural subfoveal choroidal thickness in the study group (p=0.025, r=-0.61 7). Conclusions: In patients with carotid artery stenosis, the subfoveal choroid is thinner than that in healthy controls. The subfoveal choroidal thickness increases after carotid artery stenting. Carotid artery stenting treatment increases the blood flow to the posterior ciliary artery, and the preprocedural subfoveal choroidal thickness may be a good predictor of the postprocedural peak systolic velocity of the posterior ciliary artery.
Keywords: Carotid stenosis; Stents; Ultrasonography; doppler; color; Choroid/anatomy & histology; Ciliary arteries; STENOSIS; ENDARTERECTOMY